Attitudes of elderly Austrians towards new technologies: communication and entertainment versus health and support use. - Halmdienst, Nicole; Radhuber, Michael; Winter-Ebmer, Rudolf (European Journal of Ageing, 2019)
We use data from SHARE (The Survey of Health, Ageing and Retirement in Europe) in Austria to investigate attitudes towards new technologies in information and communication technology. The technologies can significantly facilitate the daily lives of an ageing population. In Austria, in wave 6 in 2015, an additional paper-and-pencil questionnaire was implemented which asked details about attitudes towards different technological innovations. From these questions, we develop a binary attitude score which indicates positive attitudes towards new technologies. In probit estimations, the attitude score is related to different demographic and health variables. Our main results indicate that strong gender differences in attitudes towards new technologies exist: men value communication and entertainment devices more, whereas women's attitudes are more positive towards devices that include a specific health or support value. Furthermore, while older cohorts value entertainment devices less than younger ones, no such pattern exists for health and support systems.